2020
DOI: 10.1161/jaha.119.015307
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Microfibrillar‐Associated Protein 4 Attenuates Left Ventricular Remodeling and Dysfunction in Heart Failure

Abstract: Background Cardiac remodeling predisposes individuals to heart failure if the burden is not solved, and heart failure is a growing cause of morbidity and mortality worldwide. The cardiac extracellular matrix not only provides structural support, but also is a core aspect of the myocardial response to various biomechanical stresses and heart failure. MFAP4 (microfibrillar‐associated protein 4) is an integrin ligand located in the extracellular matrix, whose biological functions in the heart remain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [ 75 ], THBS4 [ 76 ], CD27 [ 77 ], LEF1 [ 78 ], CTHRC1 [ 79 ], ESR1 [ 80 ], CXCL9 [ 81 ], SERPINA3 [ 82 ], TRPC4 [ 83 ], F13A1 [ 84 ], PIK3C2A [ 85 ], KCNIP2 [ 86 ] and GPR4 [ 87 ] contributed to myocardial infarction. MFAP4 [ 88 ], ALOX15 [ 89 ], COL1A1 [ 90 ], APOA1 [ 91 ], PDE5A [ 92 ], CX3CR1 [ 93 ], THY1 [ 94 ], GREM1 [ 95 ], FMOD (fibromodulin) [ 96 ], NPPA (natriuretic peptide A) [ 97 ], LTBP2 [ 98 ], LUM (lumican) [ 99 ], IL34 [ 100 ], NRG1 [ 101 ], CXCL14 [ 102 ], CXCL10 [ 103 ], ACE (angiotensin I converting enzyme) [ 104 ], CFTR (ystic fibrosis transmembrane conductance regulator) [ 105 ], S100A8 [ 106 ], S100A9 [ 106 ], HP (haptoglobin) [ 107 ], AGTR1 [ 108 ], ATP2A2 [ 109 ], IL10 [ 110 ], EDN1 [ 111 ], TLR2 [ 112 ], MCEMP1 [ 113 ], TPO (thyroid peroxidase) [ 114 ], CD163 [ 115 ], IL18R1 [ 116 ], KCNA7 [ 117 ] and CALCRL (calcitonin receptor like receptor) [ 118 ] have an important role in HF. Li et al [ 119 ], Deckx et al [ 120 ], Ichihara et al [ 121 ] and Paik et al [ 122 ] showed that the SERPINE2, OGN (osteoglycin), AGTR2 and WNT10B promoted cardiac interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [ 75 ], THBS4 [ 76 ], CD27 [ 77 ], LEF1 [ 78 ], CTHRC1 [ 79 ], ESR1 [ 80 ], CXCL9 [ 81 ], SERPINA3 [ 82 ], TRPC4 [ 83 ], F13A1 [ 84 ], PIK3C2A [ 85 ], KCNIP2 [ 86 ] and GPR4 [ 87 ] contributed to myocardial infarction. MFAP4 [ 88 ], ALOX15 [ 89 ], COL1A1 [ 90 ], APOA1 [ 91 ], PDE5A [ 92 ], CX3CR1 [ 93 ], THY1 [ 94 ], GREM1 [ 95 ], FMOD (fibromodulin) [ 96 ], NPPA (natriuretic peptide A) [ 97 ], LTBP2 [ 98 ], LUM (lumican) [ 99 ], IL34 [ 100 ], NRG1 [ 101 ], CXCL14 [ 102 ], CXCL10 [ 103 ], ACE (angiotensin I converting enzyme) [ 104 ], CFTR (ystic fibrosis transmembrane conductance regulator) [ 105 ], S100A8 [ 106 ], S100A9 [ 106 ], HP (haptoglobin) [ 107 ], AGTR1 [ 108 ], ATP2A2 [ 109 ], IL10 [ 110 ], EDN1 [ 111 ], TLR2 [ 112 ], MCEMP1 [ 113 ], TPO (thyroid peroxidase) [ 114 ], CD163 [ 115 ], IL18R1 [ 116 ], KCNA7 [ 117 ] and CALCRL (calcitonin receptor like receptor) [ 118 ] have an important role in HF. Li et al [ 119 ], Deckx et al [ 120 ], Ichihara et al [ 121 ] and Paik et al [ 122 ] showed that the SERPINE2, OGN (osteoglycin), AGTR2 and WNT10B promoted cardiac interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, three transcripts, Apoe , Tgfbi, and Mfap4, were found interesting in cluster 6. They mediate regulation of T cell and macrophage functions, including inflammation and oxidative stress 44 , cardiac fibrosis in concert with Postn 24 , and ventricular remodeling and cardiac function, respectively 45 . As to cluster 8, we noted that a few genes were uniquely expressed with varied functions.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [66], THBS4 [67], CD27 [68], LEF1 [69], CTHRC1 [70], ESR1 [71], CXCL9 [72], SERPINA3 [73], TRPC4 [74], F13A1 [75], PIK3C2A [76], KCNIP2 [77] and GPR4 [78] contributed to myocardial infarction. MFAP4 [79], ALOX15 [80], COL1A1 [81], APOA1 [82], PDE5A [83], CX3CR1 [84], THY1 [85], GREM1 [86], FMOD (fibromodulin) [87], NPPA (natriuretic peptide A) [88], LTBP2 [89], LUM (lumican) [90], IL34 [91], NRG1 [92], CXCL14 [93], CXCL10 [94], ACE (angiotensin I converting enzyme) [95], CFTR (ystic fibrosis transmembrane conductance regulator) [96], S100A8 [97], S100A9 [97], HP (haptoglobin) [98] [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [66], THBS4 [67], CD27 [68], LEF1 [69], CTHRC1 [70], ESR1 [71], CXCL9 [72], SERPINA3 [73], TRPC4 [74], F13A1 [75], PIK3C2A [76], KCNIP2 [77] and GPR4 [78] contributed to myocardial infarction. MFAP4 [79], ALOX15 [80], COL1A1 [81], APOA1 [82], PDE5A [83] [154], OSMR (oncostatin M receptor) [155] and IL15RA [156] are involved in development of obesity, but these genes might be key for progression of HF. CTSG (cathepsin G) is a protein coding gene plays important roles in aortic aneurysms [157].…”
Section: Discussionmentioning
confidence: 99%